1996
DOI: 10.1007/bf00178610
|View full text |Cite
|
Sign up to set email alerts
|

Microbial oxidation of ebastine

Abstract: The microbial oxidation of ebastine to carebastine was investigated. Among the 15 micro-organisms examined, only the Cunninghamella strains showed the desired biotransformation. Cunninghamella blakesleeana oxidised the substrate within 7 days, via the intermediates alcohol and aldehyde, mainly to carebastine, the corresponding carboxylic acid. Optimisation of the culture conditions increased the yield from initially 10% up to a reproducible 40%. For the synthesis of carebastine a substrate concentration of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The study of polyP accumulation by microorganisms growing under differential conditions is important to understand the mechanism of biosynthesis, functions, accumulation and further development of removing processes of environmental pollulants (33,44,65,71).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of polyP accumulation by microorganisms growing under differential conditions is important to understand the mechanism of biosynthesis, functions, accumulation and further development of removing processes of environmental pollulants (33,44,65,71).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that addition of phosphate to cells previously subjected to phosphate starvation also induces rapid accumulation of PolyP; a phenomenon known as polyP overplus (42,65). PolyP are present in large amounts in cells growing on a complete medium with high orthophosphate content.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations